2015
DOI: 10.1161/circep.115.003199
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Suppression of Atrial Fibrillation by Botulinum Toxin Injection Into Epicardial Fat Pads in Patients Undergoing Cardiac Surgery

Abstract: Background-Animal models suggest that the neurotransmitter inhibitor, botulinum toxin, when injected into the epicardial fat pads can suppress atrial fibrillation inducibility. The aim of this prospective randomized double-blind study was to compare the efficacy and safety of botulinum toxin injection into epicardial fat pads for preventing atrial tachyarrhythmias. Methods and Results-Patients with history of paroxysmal atrial fibrillation and indication for coronary artery bypass graft surgery were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 59 publications
1
72
0
1
Order By: Relevance
“…Botulinum toxin injection in two fat pads suppressed AF inducibility at 1 week, but this disappeared at 2 weeks and 3 weeks. In human randomized clinical trials, however, botulinum toxin injected in the epicardial fat pads during cardiac surgery not only suppressed postoperative AF but also reduced the incidence of AF for at least 1 year . The prolonged benefit suggests that botulinum might induce GP remodeling.…”
Section: Neuromodulation Of Ganglionated Pleximentioning
confidence: 99%
“…Botulinum toxin injection in two fat pads suppressed AF inducibility at 1 week, but this disappeared at 2 weeks and 3 weeks. In human randomized clinical trials, however, botulinum toxin injected in the epicardial fat pads during cardiac surgery not only suppressed postoperative AF but also reduced the incidence of AF for at least 1 year . The prolonged benefit suggests that botulinum might induce GP remodeling.…”
Section: Neuromodulation Of Ganglionated Pleximentioning
confidence: 99%
“…showed that post‐CABG injection of BTX led to a decreased incidence of AF 30 days after surgery . More recently, the same group presented data showing that this difference was sustained for up to 1 year after surgery . The protective mechanism of BTX has been theorized to be due to its effects on acetylcholine release .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, vulnerability to AF may not be reflected by programmed atrial stimulation. Although this may be debatable, studies have shown a correlation between AF inducibility using programmed atrial stimulation and the clinical burden of AF …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be reminiscent of data originally presented at the Annual Sessions in which the AF-free period after epicardial fat pad botulinum toxin injection in patients undergoing open heart surgery long outlasted the autonomic effects. 13 Conclusions AF has been a robust subject at many of the Heart Rhythm Sessions, and the 2017 Scientific Sessions were no exception. I hope these ''highlights,'' as subjective as they may be, spark a continuing interest in AF investigation, but more importantly, that they translate into improved care for our patients.…”
Section: Antiarrhythmic Therapy Post-ablation For Afmentioning
confidence: 99%